Pore-Scale Simulations of Particle Transport for Groundwater Remediation: the Effect of Gravitational Settling - E. Crevacore; G. Boccardo; A. Grillo; D. Marchisio; R. Sethi (Chemical Engineering Transactions, 2017)
In this work, we investigate particle deposition efficiency in porous media by way of pore-scale computational fluid dynamics simulations. First, we show how to employ a novel methodology of algorithmic generation of porous media to build the computational domain for our simulations, representing a realistic random packing of monodisperse spheres. Then, we focus on the effect of gravitational settling on particle deposition, comparing our results with the well-known simplified theoretical laws, showing how pore-scale numerical experiments can improve the prediction accuracy of these laws but, most of all, help gain fundamental insights in the physical mechanisms at work.